The impact of negative COVID-19 experiences on cancer survivors’ health-related quality of life and psychological distress: a moderated mediation model - Noriega Esquives, Blanca S.; Natori, Akina; Antoni, Michael H.; Otto, Amy K.; Prinsloo, Sarah; Wagner, Richard W.; Gomez, Telma I.; Hathaway, Cassandra A.; Ulrich, Cornelia M.; Peoples, Anita R.; Cohen, Lorenzo; Penedo, Frank J. (Frontiers in Psychology, 2024)
Introduction Cancer survivors experienced poorer health-related quality of life (HRQoL) and greater psychological distress during the COVID-19 pandemic than those without cancer. However, the underlying mechanisms that may explain how negative experiences during the pandemic are associated with distress and HRQoL remain unknown. We examined whether psychosocial risk factors (i.e., healthcare disruption, disruption to daily activities and social interaction [DDASI], and financial hardship) mediated the relationship between negative COVID-19-related experiences and cancer survivors’ HRQoL and psychological distress (i.e., depressive symptoms, and anxiety) and whether the mediating effects were moderated by psychosocial protective factors (i.e., stress management ability and social support). Methods A total of 9,651 cancer survivors completed a questionnaire assessing negative COVID-19-related experiences, psychosocial and practical experiences, and HRQoL. Conditional process analysis was used to evaluate the proposed moderated mediation models. Results Participants had a mean age of 63.8 years (SD = 12.3) and were mostly non-Hispanic White (82.3%). DDASI and financial hardship mediated the relationship between negative COVID-19-related experiences and cancer survivor’s HRQoL and psychological distress. Stress management ability buffered the indirect effect of DDASI on cancer survivors’ HRQoL and psychological distress. Social support buffered the indirect effect of financial hardship on HRQoL and depressive symptoms. Conclusion Financial resources and social interactions may buffer negative effects of major disruptions such as the COVID-19 pandemic. Future studies should assess the longitudinal impact of these associations.